Nested stromal epithelial tumor of liver presenting with Cushing syndrome: A Rare case Report - Bita Geramizadeh; Hamidreza Foroutan; Ali Foroutan; Mohammadreza Bordbar (Wolters Kluwer Medknow Publications, 2012)
Nested stromal and epithelial tumor of the liver is an extremely rare pediatric hepatic tumor. To the best of our knowledge, about 25 cases have been reported in the English literature so far, few of which accompanied with Cushing syndrome. Herein we report our experience with an 8-year-old boy presented with Cushing's syndrome because of ectopic ACTH production by this tumor.